Drop dead healthy eaudiobook One man's humble quest for bodily perfection. - Jacobs, A.J (Recorded Books, Inc., 2014)
Heralded as the king of "immersion journalism," New York Times best-selling author A.J. Jacobs sets off on his most daunting experiment yet. In Drop Dead Healthy, Jacobs attempts to become the healthiest man alive—at times to his (extremely patient) wife's chagrin. Relating his tussle with the often nonsensical world of dieting and exercise advice, Jacobs goes to excruciating (and hilarious) lengths in the pursuit of perfection.